Smart Campus Ecosystems For Efficient And Sustainable Information Technology Governance in Nigerian Islamic Education - Abdul Khobir; Oluwakemi Racheal Oshinowo; Moses Adeolu Agoi (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2026)
Innovative campus ecosystems represent a paradigm shift in higher education management by integrating advanced digital technologies into teaching, administration, and campus operations. Unlike traditional campuses that rely on fragmented, manual systems, smart campuses are interconnected digital ecosystems supported by the Internet of Things (IoT), artificial intelligence (AI), data analytics, and robust information and communication technology (ICT) infrastructure in the context of Nigerian Islamic education. The primary objective of this study is to investigate how innovative campus ecosystems contribute to economic efficiency and financial sustainability in higher education institutions, while also highlighting the role of effective IT governance. This paper employs a qualitative literature review to synthesise recent scholarly research on smart campus implementation, focusing on the economic, technological, and governance dimensions. The analysis explores how intelligent energy management, automated administrative processes, and predictive analytics enhance operational efficiency, reduce costs, and improve financial planning. The findings suggest that innovative campus ecosystems significantly enhance institutional efficiency, support evidence-based decision-making, and promote innovation and collaboration among stakeholders. However, their implementation faces challenges related to governance complexity, funding limitations, digital inequality, and cybersecurity risks. The study concludes that strong IT governance, strategic leadership, and long-term policy alignment are crucial to achieving sustainable and innovative campus development and to advancing future empirical research in Nigerian Islamic education.